Hunger as protest. The "Fasting women" of Palermo (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
This article examines the unique role of women in the Italian anti-mafia movement, highlighting their emphasis on collective action and cooperation over individual recognition. Women’s involvement challenges stereotypical roles and extends the movement’s reach beyond personal experiences of victimization to include broader civic responsibilities. The study calls for a deeper recognition of women’s contributions, situating their activism within broader feminist movements for justice, equality and democratic reform.
Keywords: mafia; woman; anti-mafia movement; social movements; feminist movements